Disentangling Different Patterns of Business Cycle Synchronicity in The EU Regions - Ageliki Anagnostou; Ioannis Panteladis; Maria Tsiapa (European Regional Science Association (ERSA), 2012)
The present paper discourses on how European integration and gradual enlargement has affected the synchronicity in business cycles in EU regions. The analysis, which is conducted on annual data at the NUTSII level, is based on the following grounds: First, it examines the degree of synchronicity in business cycles in EU regions associated with specific spatial and economic characteristics that explain, to a large extent, synchronisation dynamics. Secondly, the study investigates the existence of a time-varying national `border effect', with eventually differentiated dynamism among the old and the new EU member states. For this purpose a dynamic Panel VAR model is employed in order to investigate the impact of spatial variables and productions structures on business cycles taking into consideration the variation in time and cross regions specific characteristics attributed to the integration process of these regions.
Keywords: 330